PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA N 12 PADANG TAHUN PEMBELAJARAN 2022/2023 - Anisa Alya Utami (Jurnal Edukasi dan Penelitian Matematika, 2022)
The ability to solve problems is one of the goals of learning mathematics and should develop optimally in students. But in fact, students in class XI MIPA SMA N 12 Padang's math problem solving ability is still low. This can be seen in students' responses when asked questions containing problem-solving steps, indicating that students failed to solve math problems correctly. One of the efforts to overcome these problems is to use a Two Stay Two Stray (TSTS) type of cooperative learning model.Keywords – Two Stay Two Stray (TSTS), Mathematics Problem Solving